Partisipasi Masyarakat dalam Pengelolaan Dana Desa (Analisis Kasus Kepemimpinan Kepala Desa Gadingrejo, Kecamatan Gading Rejo, Kabupaten Pringsewu) - Hayatul Aulia Arozza; Dian Kagungan; Devi Yulianti (Jurnal Administrativa, 2020)
The village head carries out the tasks assigned by the central government to regulate and carry out these policies made in the framework of joint development with the community towards a prosperous society. Through Mr. Gunawan's leadership, Gading Rejo Village carried out development using the Village Fund in accordance with development priorities which were jointly developed with the community. Development carried out using village funds is the construction of roads, construction of water culverts, water irrigation channels, monuments, and community activity units. Village community development is a development movement based on community self-help and mutual cooperation. The type of research used in this research is descriptive type with a qualitative approach, data collection techniques, observation, interviews, documentation. The results of this study indicate that the leadership of the village head Gadingrejo to increase community participation in the management of village funds focuses more on the democratic leadership style, the leadership style of the Gadingrejo Village Head obtains high direction of support from the community, in guiding the community, the village head gives instructions to the community such as mechanisms in the field and what is needed in development, so that the duties and functions of the village head can be carried out properly.